Incidental abnormal CT scan findings during transcatheter aortic valve implantation assessment: incidence and implications. Issue 2 (27th August 2018) - Patel, Akshay; Mahendran, Kajan; Collins, Michael; Abdelaziz, Mahmoud; Khogali, Saib; Luckraz, Heyman
Abstract : Objectives: The aim of this retrospective series is to describe the prevalence and clinical significance of the incidental findings found during pre–transcatheter aortic valve implantation (TAVI) work-up and to ascertain the clinical course of such patients. Methods: Consecutive patients undergoing TAVI from 2013 to 2015 where a TAVI CT assessment was performed (n=138) were included in the study. All incidental findings that were not expected from the patient's history were discussed at the TAVI multidisciplinary meeting in order to ascertain the clinical significance of said findings and whether they would alter the proposed course of treatment. Mortality data were determined by careful retrospective case note and follow-up appointment analysis. Results: Seventy-eight patients (57%) were found to have incidental findings on pre-TAVI CT scan. The majority of patients had benign pathology with high incidence in particular of diverticular disease, pleural effusions, gallstones, hiatus hernia and degenerative spinal disease. Vascular pathology such as superior mesenteric, renal and iliac artery stenoses and abdominal aortic aneurysm was detected in seven patients. In terms of long-term mortality data, we found no significant difference between those with incidental findings and those without (p=0.48). Survival as assessed by Kaplan-Meier analysis showed no significant difference between those with and without incidental abnormal CT scan findings (p=0.98). Conclusions: Incidental findings with potential for malignancy are common in an elderly, comorbid population. Ultimately, clinical correlation and prognosis must be swiftly ascertained in order to streamline the patients down the appropriate management pathway while avoiding unnecessary delay for treatment of their aortic stenosis.